Glucose Uptake in Rat Skeletal Muscle L6 Cells Is Increased by Low-Intensity Electrical Current Through the Activation of the Phosphatidylinositol-3-OH Kinase (PI-3K) / Akt Pathway - Shuichiro Yano; Saori Morino-Koga; Tatsuya Kondo; Mary Ann Suico; Tomoaki Koga; Yuichiro Shimauchi; Shingo Matsuyama; Tsuyoshi Shuto; Takashi Sato; Eiichi Araki; Hirofumi Kai (Elsevier, 2011)
Activation of Akt by insulin is transmitted via phosphatidylinositol-3-OH kinase (PI-3K) and enhances glucose uptake. The PI-3K/Akt signaling is diminished in insulin resistance. Thus, approaches that activate PI-3K/Akt signaling leading to improved glucose uptake may ameliorate hyperglycemia. Here we showed that low-intensity electrical current or mild electrical stimulation (MES) activated the PI-3K/Akt signaling and increased the glucose uptake in rat skeletal muscle (L6) cells. The glucose uptake enhanced by MES in muscle cells, the major cells involved in glucose disposal, suggests MES may have a possible beneficial effect on hyperglycemia. Keywords:: mild electrical stimulation, phosphatidylinositol-3-OH kinase (PI-3K) / Akt, glucose uptake